2021
DOI: 10.4049/jimmunol.2001178
|View full text |Cite
|
Sign up to set email alerts
|

Ubc13 Promotes K63-Linked Polyubiquitination of NLRP3 to Activate Inflammasome

Abstract: NLRP3 inflammasome plays an important role in innate immune system through recognizing pathogenic microorganisms and danger-associated molecules. Deubiquitination of NLRP3 has been shown to be essential for its activation, yet the functions of Ubc13, the K63-linked specific ubiquitin-conjugating enzyme E2, in NLRP3 inflammasome activation are not known. In this study, we found that in mouse macrophages, Ubc13 knockdown or knockout dramatically impaired NLRP3 inflammasome activation. Catalytic activity is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Recently, Ubc13 was also shown to associate with NLRP3 , catalyze K63-linked ubiquitination of NLRP3 and activate the inflammasome [ 64 ] ( Figure 2 , Figure 3 ). Upon stimulation with LPS and ATP, BMDMs from Ubc13 deltaMye mice (which specifically lack Ubc13 in myeloid cells; Ubc13 +/– ) showed diminished secretion of IL-1β and impaired caspase-1 maturation compared with WT ( Ubc13 +/+ ) controls [ 64 ]. Endogenous Ubc13 interacted with NLRP3 in BMDMs, correlating with inflammasome activation, NLRP3 was K63-ubiquitinated in the presence of WT Ubc13 but not mutant Ubc13C87A [ 64 ].…”
Section: K63 Ubiquitination In Immune Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ubc13 was also shown to associate with NLRP3 , catalyze K63-linked ubiquitination of NLRP3 and activate the inflammasome [ 64 ] ( Figure 2 , Figure 3 ). Upon stimulation with LPS and ATP, BMDMs from Ubc13 deltaMye mice (which specifically lack Ubc13 in myeloid cells; Ubc13 +/– ) showed diminished secretion of IL-1β and impaired caspase-1 maturation compared with WT ( Ubc13 +/+ ) controls [ 64 ]. Endogenous Ubc13 interacted with NLRP3 in BMDMs, correlating with inflammasome activation, NLRP3 was K63-ubiquitinated in the presence of WT Ubc13 but not mutant Ubc13C87A [ 64 ].…”
Section: K63 Ubiquitination In Immune Signalingmentioning
confidence: 99%
“…Upon stimulation with LPS and ATP, BMDMs from Ubc13 deltaMye mice (which specifically lack Ubc13 in myeloid cells; Ubc13 +/– ) showed diminished secretion of IL-1β and impaired caspase-1 maturation compared with WT ( Ubc13 +/+ ) controls [ 64 ]. Endogenous Ubc13 interacted with NLRP3 in BMDMs, correlating with inflammasome activation, NLRP3 was K63-ubiquitinated in the presence of WT Ubc13 but not mutant Ubc13C87A [ 64 ].
Figure 3 Ubiquitination signaling pathways in innate and adaptive immunity.
…”
Section: K63 Ubiquitination In Immune Signalingmentioning
confidence: 99%
“…Additionally, Ubc13 transduces the NF-κB signal by interacting with TNF receptor-associated factor 6 (TRAF6) [99]. A recent study found that Ubc13 acts as a positive regulator for NLRP3 inflammasome activation, as Ubc13 deficiency significantly reduced NLRP3 inflammasome activation [100]. The study also revealed that Ubc13 interacts with NLRP3 to induce K63-linked polyubiquitination at K565 and K687 sites.…”
Section: Ubc13mentioning
confidence: 95%
“…Multiple E3 negative regulators that affect NLRP3 levels or activation have been identified including FBXL2 (Han et al, 2015), PARKIN (Kang et al, 2016), and TRIM31 (Song et al, 2016), which provide a signal for proteasomal degradation, MARCH7 (Yan et al, 2015), which provides a signal for degradation by autophagy, and ARIH2 (Kawashima et al, 2017) and CUL1 (Wan et al, 2019), which bind and ubiquitinate NLRP3 to maintain its inactive state. Positive regulation of NLRP3 by the ubiquitin system has been observed with the interplay of numerous E3 enzymes including PELI2 (Humphries et al, 2018), TRAF6 (Xing et al, 2017), and TRIM33 (Weng et al, 2014), the E2 enzyme UBC13 (Ni et al, 2021), as well as the deubiquitinating enzymes BRCC3/ABRO1 (Py et al, 2013;Ren et al, 2019), USP7 and USP47 (Lopez-Castejon et al, 2013), and UCHL5 (Kummari et al, 2015). Negative regulation of the NLRP3 and AIM2 inflammasomes by ubiquitination of ASC promoting proteasomal degradation has also been shown by the TRAF6 E3 enzyme (Chiu et al, 2016) which, interestingly, has been shown to be a positive regulator of NLRP3.…”
Section: Ubiquitination and Deubiquitinationmentioning
confidence: 99%